A survey demonstrates limited palliative care structures in paediatric nephrology from the perspective of a multidisciplinary healthcare team - Thumfart, Julia Angelika; Bethe, Dirk (Acta paediatrica, 2019)
Aim Children and adolescents with end-stage renal disease face a high morbidity and mortality. Palliative care provides a multidisciplinary approach to reduce disease burden and improve quality of life. This study evaluated concepts and current structures of palliative care from the perspective of a multidisciplinary paediatric nephrology team including physicians, nurses and psychosocial health professionals. Methods Evaluation was done by an online survey sent to the members of the German Society of Nephrology and to the nurse managers of German paediatric dialysis centres between April 9, 2018 and May 31, 2018. Results Out of the 52 respondents, 54% were physicians, 21% nurses and 25% psychosocial health professionals. The quality of actual palliative care service was rated as moderate (3.3 on a scale from one to six). Specialised palliative care teams (54%) and the caring paediatric nephrologist (50%) were considered as primarily responsible for palliative care. Two thirds wished for training in palliative care. In only 15% of the respondents’ centres, palliative care specialisation existed. Conclusion Palliative care structures in paediatric nephrology were not sufficient in the view of the multidisciplinary healthcare team. Therefore, efforts should be taken to integrate palliative care into the routine treatment of children and adolescents with chronic kidney diseases.
First published: 11 December 2018
Gesehen am 07.08.2019